(untitled) (Journal of the College of Basic Education, 2022)
The current search targeted:1- Knowing the level of future anxiety among the students of the College of Basic Education according to the gender variable: a- males b- females.2- Knowing the level of cognitive self-regulation among the students of the College of Basic Education according to the gender variable: a- males b- females.3- Know the correlation between future anxiety and cognitive self-regulation according to the gender variable (males - females).The research sample consisted of (200) students (100) males and (100) females, who were randomly selected from the fourth grade students from the College of Basic Education at Al-Mustansiriya University for the academic year 2011-2012 / morning study.